Effect of bFGF gel nano-sustained-release technology on rehabilitation effect of adult heart valve replacement - Huang, Dong; Wang, Di; Yin, Chengyong; Tian, Jun; Peng, Fei; Chen, Feiyun; Yang, Baihui (Cellular and Molecular Biology, 2022)
the Due to the rapid improvement of economic level, aging and lifestyle changes, the incidence of valvular heart disease continues to increase, and the bFGF gel nano sustained-release technology plays an important role in the rehabilitation of adult heart valve replacement patients. The purpose of this article is to investigate the effect of bFGF gel nano-slow release technology on the rehabilitation effect of adult heart valve replacement patients. The research object was selected from all cases of valve replacement surgery from January 2019 to January 2020, and 216 patients were divided into experimental group and control group, the experimental group carried out the sustained release of bFGF gel nanospheres. The experimental group was 49.76±8.13 years old, including 94 cases of rheumatic heart disease, 13 cases of degenerative valvular disease, and 3 cases of congenital valvular disease, a total of 110 cases. Heart performance tests were performed respectively. The results showed that the incidence of atrial fibrillation, left ventricular hypertrophy and ST-segment depression of 0.1m V in the experimental group were 32.19%, 34.48%, and 19.84%, while the corresponding data in the control group were 62.78%, 52.07%, and 45.87%. It can be seen that bFGF gel nano sustained-release technology is of great significance for the rehabilitation of adult heart valve replacement patients.